Arthroscopic Reduction-Association of the Scapholunate with an Absorbable Screw - Jorge, João Torrinha; Ferrão, Ana; Alves, Sandra; Caetano, Ruben; Teixeira, Frederico (Journal of Wrist Surgery, 2018)
Background The treatment of chronic scapholunate instability is yet a controversial topic. Arthroscopic reduction-association scapholunate technique is a minimally invasive option in which a stable pseudoarthrosis at the scapholunate joint is obtained, allowing some degree of movement while maintaining the normal alignment of the wrist. The purpose of this study was to review the results of arthroscopic reduction-association scapholunate with an absorbable screw.Methods We retrospectively evaluated patients with dynamic or static, but reducible, chronic scapholunate instability who underwent arthroscopic reduction-association scapholunate between 2012 and 2015. An absorbable headless compression screw was used in the technique.Results A total of 33 patients (21 males, 12 females) were included. Average follow-up time was 17 months. At final follow-up, the average postoperative Disabilities of the Arm, Shoulder and Hand (DASH) score was 18 (range, 8–46). The average postoperative grip strength was 30 kg, 73% of the uninjured side. The average extension-palmar flexion arc was 112 degrees, 79% of the uninjured side. The scapholunate angle decreased from 70 degrees preoperatively to 52 degrees postoperatively. In the cases of static lesion, the scapholunate interval decreased from 4.1 mm preoperatively to 2.8 mm at final follow-up. One patient had a breakage of the screw at 4 months, four developed a complex regional pain syndrome, one had a prominence of the screw at the waist of the scaphoid, and four maintained symptoms of instability. From these 10 patients, 5 were submitted to revision surgery.Conclusion The arthroscopic reduction-association technique is capable of maintaining the reduction of the scapholunate joint and of improving symptoms, while preserving range-of-motion. The use of an absorbable screw is an option in this technique, and may diminish screw-related complications.
Keywords: scapholunate dissociation; carpal instability; reduction-association scapholunate; arthroscopic surgery; absorbable screw